Investigation on surface roughness and MRR in WEDM of titanium grade 7 (Ti-0.15Pd) alloy using statistical techniques / H. R. Basavaraju, S. S. Manjunatha and R. Suresh - H.R., Basavaraju; S.S., Manjunatha; R., Suresh (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Wire Electric Discharge Machining (WEDM) of Titanium grade alloys with coated electrodes has several advantages over the traditional machining process such as increased productivity, reduction of processing cost, and improved material properties. The main objective is to create a relationship between WEDM parameters such as Pulse-on (TON), Pulse-off (TOFF), and Indicated Power (IP) with surface roughness (Ra) and Material Removal Rate (MRR). In the present work, the performance of zinc-coated brass electrodes for WEDM of Titanium Grade-7 alloy was assessed and optimized with statistical technique. ANOVA analysis is used to analysis of the MRR and Ra and validated with regression. The ANOVA analysis results indicated that TON is the highest statistically significant and followed by TOFF and IP on MRR and surface roughness. The optimum combination of higher IP(6 A) and TON time(60 µs) and lower TOFF time (12 µs) is lucrative for a higher MRR of 8.5682 mm3/min and lower surface roughness of 1.66 µm. The SEM images showed homogeneous solidification, columnar grain structure, recast layer surface, and minor surface crack density were noticed at higher cutting conditions. The predicted model and confirmation test results were close to each other with minimum error.